The Development of Islamic Study Through The Study of Figures: Significance and Methodology - Ngainun Naim (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article describes the role of figure studies in Islamic studies. The study of real figures has been around for a long time and developed in the Islamic Religious Higher Education (PTKI). However, it takes various methodological and strategic steps to make its existence enrich the treasures of Islamic studies. Within this framework, this paper provides an affirmative perspective on the significance, methodology, and contributions of the study of the characters in Islamic studies. The study used in this paper is a review of literature that is structured in such a way that the basis of argumentation developed from the thinking of the experts of Islamic studies and other experts who have attention to the study of figures. This article is expected to provide a reinforcing perspective on the importance of theoretical reinforcement and methodological study of figures.